Accelerated and “natural” production-system effects on performance and carcass traits - Veloso, L.; Loe, E.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sixteen crossbred steers were used to compare performance and carcass characteristics of animals from accelerated and “natural” cattle production systems. Steers in the accelerated group (8 head) were implanted with Component TE-S (120 mg of trenbolone acetate, 24 mg estradiol), and received 200 mg/steer daily of ractopamine-HCl (Optaflexx) during the last 33 days of feeding. Tylan and Rumensin were also fed to the accelerated group. “Natural” steers were not implanted and were not given feed additives. Steers in the accelerated group had improved gain; heavier final weights; heavier carcasses; larger ribeye areas; and less kidney, pelvic, and heart fat. “Natural” cattle had better quality grades, but would require a $3/cwt carcass premium to offset the performance advantages of accelerated cattle.
Keywords: Beef; Accelerated production system; Natural production system; Performance; Carcass traits